Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and the Yahoo Answers website is now in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

How do I solve this algebraic equation?

What are the steps involved in answering the following equation?

Sove the x:

x(2x + 1) - 2 (x - 3) = 2x (x + 1)

Thanks in advance.

5 Answers

Relevance
  • ?
    Lv 4
    1 decade ago
    Favorite Answer

    1. Start with distributing...

    distribute the x to the 2x + 1

    the -2 to the x - 3

    and then the 2x to the x + 1

    2. Subtract 2x squared from both sides

    Leaves you wish 1x - 2x + 6 = 2x

    3. Add/ subtract like terms

    1x - 2x = -1x

    Leaves -1x + 6 = 2x

    4. Add 1x to both sides

    Leaves you with 6 = 3x

    5. Divide each side by three and get what x equals

  • 1 decade ago

    First remove the brackets

    Gives

    2x^2 + x - 2x + 6 = 2x^2 + 2x

    Now gather like terms together

    Remember that when a number crosses the equals sign then minus becomes plus and plus becomes minus

    All that is left

    3x = 6

    x = 6/3

    So x = 2

  • 1 decade ago

    Hey,

    Multiply everything, then move all the x terms to one side and simplify.

    x(2x + 1) - 2 (x - 3) = 2x (x + 1)

    2x^2 + x - 2x +6 = 2x^2 + 2x

    2x^2 -2x^2 + x - 2x - 2x = -6

    x - 4x = -6

    -3x = -6

    x = -6/-3

    x = 2

    You're welcome!

  • 1 decade ago

    2x^2+x-2x+6=2x^2+2x

    x=-6

  • 1 decade ago

    distribute the x then solve for its value.

Still have questions? Get your answers by asking now.